Detection of Bovine Alpha-S1-Casein in Term and Preterm Human Colostrum with Proteomic Techniques. (April 2013) - Orrù, S.; Di Nicola, P.; Giuliani, F.; Fabris, C.; Conti, A.; Coscia, A.; Bertino, E.
Due to increased social awareness of allergens and population hyper-sensitization, the reported incidence of allergic reactions to food allergens has increased over the past two decades. Cow's milk proteins (CMPs) are among the most common food allergens. The aim of this study was to use proteomics techniques to investigate cow's milk allergens in both full-term human colostrum and in preterm newborns' mothers - where both groups showed no prior allergen detection – in order to understand whether cow's milk allergens could be a cause of sensitization established through lactation. The most relevant finding was the detection of the intact bovine alpha-S1-casein in both term and preterm colostrum. Using techniques detailed in this paper and which allowed for direct protein identification, β-lactoglobulin was not detected in any of the colostrum samples. According to our results, bovine alpha 1 casein is considered a major cow's milk allergen, is readily secreted in human milk, and so could be considered a possible cause of sensitization in exclusively breastfed infants.